Analisa Jenis Interaksi Masyarakat dengan Akuisisi Data Sosial Media Pemerintah KAB/Kota Provinsi Riau: Analisa Jenis Interaksi Masyarakat dengan Akuisisi Data Sosial Media Pemerintah - Nina Fadilah Najwa; Yuliska Yuliska; Khairul Umam Syaliman (Politeknik Caltex Riau, 2020)
This study aims to analyze the type of interaction which is done by acquiring City/District Government’s Facebook Fan page. The acquisition of Facebook Fan page is performed by identifying the number of followers, the number of likes of the page, the number of postings, the number of comments, the number of shared postings and the number of likes of postings. We perform the acquisition in 90 days. Based on the result of data acquisition on 13 Cities/Districts in Riau Province, it indicates that 100% City/District Governments have performed One-Way Push Interaction and 70% of them classified as Two-Way Pool interaction. As for network co-designer of service Interaction, we found that Bengkalis District is the most active in implementing this type of interaction. Based on the results of analyzing the type of interaction between citizens and local governments in Riau Province, most of the Social media Fan Page of local governments are passive. The Collaboration of governments and citizens, which is based on the number of shared postings is classified as low. The next study may discuss the strategy that can be implemented by the governments to maximize the use of social media as media to interact and communicate with the citizens.